Missing pieces in the story of a caterpillar fungus — Ophiocordyceps sinensis - Siran Liang (IMA Fungus)
Abstract Ophiocordyceps sinensis (syn. Cordyceps sinensis) is a peculiar caterpillar fungus. It is not only known for its extraordinary medicinal values, which cover a wide spectrum of illnesses ranging from fatigue to cancer, but also for its fascinating life-story (Yeh & Lama 2013). Unlike many medicinal products, advertisements for “Cordyceps” do not solely promote its medicinal value, but also the origin of its production. Retailers often employ snowy mountains, Tibetan script, Tibetan people, blue sky and green meadows to advertise their products. Te imagined geography delivers a message to consumers that it is a natural wonder that comes from a Xanadu, a distant, exotic, untouched and unpolluted place. Te description of its production site is not meant to deceive the consumers, but it is only one piece of the story. Behind the veil of Ophiocordyceps commodification, we see missing pieces from a personal experience during a two-month-long field research in the eastern Tibetan region in summer 2018: Tibetan harvesters, a harsh climate, the declining Ophiocordyceps populations, plastic packaging and aluminum cans loitering the meadows. All these are also part of the production story.